2016
DOI: 10.2147/tcrm.s96606
|View full text |Cite
|
Sign up to set email alerts
|

Dysfunction of the thyroid gland during amiodarone therapy: a study of 297 cases

Abstract: AimThis study aims to explore and compare the efficacy of radioiodine treatment (RIT) in hyperthyroid and euthyroid patients who have been treated with amiodarone (AM) in the past or are currently undergoing AM treatment. Clinical observation of a group of patients with amiodarone-induced hypothyroidism during a 12-month follow-up period was used for comparison.DesignThis was a observational, two-centered study. Patients were assessed at baseline and at 2 months, 6 months, 8 months, and 12 months after RIT.Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 38 publications
(44 reference statements)
0
9
0
1
Order By: Relevance
“…This approach may be justified in patients who are unsuitable for thyroidectomy and need to continue amiodarone therapy [48]. A recent study on 297 patients has shown a benefit of RAI treatment remarkably when amiodarone therapy is continued or needs to be restarted [49]. The study suggested RAI even in euthyroid patients, because it helps continuation, reintroduction and/or adherence to long-term amiodarone treatment.…”
Section: Managementmentioning
confidence: 99%
“…This approach may be justified in patients who are unsuitable for thyroidectomy and need to continue amiodarone therapy [48]. A recent study on 297 patients has shown a benefit of RAI treatment remarkably when amiodarone therapy is continued or needs to be restarted [49]. The study suggested RAI even in euthyroid patients, because it helps continuation, reintroduction and/or adherence to long-term amiodarone treatment.…”
Section: Managementmentioning
confidence: 99%
“…Alternative methods of treatment of AIT (used in adult patients -data supporting usage in paediatric patients are lacking) include: lithium carbonate, radioactive iodine therapy, plasmapheresis, total thyroidectomy, and embolisation of the thyroid artery [18][19][20]. According to the latest recommendations, complete thyroidectomy or radioactive iodine therapy as a radical treatment is indicated in hyperthyroidism, regardless of its type, allowing rapid achievement of euthyreosis and possible re-inclusion of amiodarone into the treatment, especially in type 1 AIT [21,14]. The special role of total thyroidectomy, performed in patients with a severe condition due to cardiac causes and not responding to pharmacological treatment of hyperthyroidism, without first obtaining euthyroidism, is underlined [14].…”
Section: Discussionmentioning
confidence: 99%
“…However, there are reports in the literature that it is effective and justified not only in cases of normal or increased radioiodine uptake, but also in a situation when radioiodine uptake is lowered [18]. Few data indicate effectiveness of rhTSH-aided radioiodine therapy [4,21]. However, the latest recommendations do not recommend this procedure [14].…”
Section: Discussionmentioning
confidence: 99%
“…While hyperthyroidism may induce AF, the thyroid gland function is often not known during the first AF presentation, hence amiodarone must be used with caution to prevent a thyrotoxic crisis. 12 …”
Section: Therapeutic Options For Rate Control In Atrial Fibrillation mentioning
confidence: 99%